IMPROVING THE FISCAL ROLE OF LOCAL TAXES AND FEES IN THE FORMATION OF REVENUES OF LOCAL BUDGETS - Mykhailenko , S.V. (The actual problems of regional economy development, 2017)
Decentralization of power and a significant empowerment of local communities, the provision of fiscal autonomy and financial independence of local budgets, strengthening of material and financial base of local self-government is an objective need for Ukraine. In modern conditions of development of the state economy enhancing the role of local taxes and fees and an increase in the revenue part of local budgets at their expense is the main lever for increased financial independence and financial autonomy of local authorities. Local taxation system must provide local authorities with financial resources to fulfill its mandate. However, local governments are not able to fully satisfy their functions and tasks from local taxes and fees, which requires further research in this area. The aim of the article is to study the role of local taxes and fees in the formation of revenues of local budgets of Ukraine taking into account the innovations of the budget and tax legislation, and making proposals on the reform of local taxation system. The paper used the methods of theoretical and practical generalization, systematic and comparative analysis, statistical methods, grouping, table-graphics. The study reviewed the historical aspects of the formation and development of local taxes and fees in Ukraine, analyzed the innovation budget and tax legislation with respect to the local tax system, their positive and negative consequences. The analysis of the composition and structure of local taxes and fees in the incomes of local budgets of Ukraine for five years. The role of local taxes and fees in the local budget revenues, tax revenues and GDP. The measures to further reform the system of local taxes and fees in the country.